Chemical Sensors and Biosensors: Fundamentals and Applications - Banica F.-G. Florinel-Cabriel (Chichester, John Wiley & Sons, Ltd., 2012)
Chemical sensors are self-contained analytical devices that provide real-time information on chemical composition. A chemical sensor integrates two distinct functions: recognition and transduction. Such devices are widely used for a variety of applications, including clinical analysis, environment monitoring and monitoring of industrial processes. This text provides an up-to-date survey of chemical sensor science and technology, with a good balance between classical aspects and contemporary trends.